Ojibwe materials, Benjamin Franklin Papers - Rogers, Robert, 1731-1795 (1767)
Letter to Benjamin Franklin encloses a 27-page estimate and account of the peltry and fur trade of the district of Michilimakinac. The estimate gives the probable cost of carrying on the trade with the outposts as £60,898. If the trade be confined to the one post at Michilimakinac the cost would be much smaller but the Spaniards would work up the outposts. Greatly favors extension of the trade and recommends a plan of civil government for the district.